The Role of Biostatistics in Personalized Medicine: Challenges and Opportunities - Khayoun Khansh, Hussein Fadel; abid abid alkarim, Mohammed saad; Hussein Hassan Saleh, Mohammed Abdul; Kamel Wahid, Suma Jumaa; Jabr Amana, Moaml Jawad (American Journal of Botany and Bioengineering, 2025)
Personalized medicine is an emerging practice of medicine that uses an individual's genetic profile to guide decisions made regarding the prevention, diagnosis, and treatment of disease. Biostatisticians will play a key role in enabling personalized medicine to transform the healthcare system from the conventional "one-size-fits-all" paradigm to individualized patient care. This chapter discusses the impact of personalized medicine on biostatistics research contributions and implications for graduate education in biostatistics. Major challenges and future opportunities of biostatistics research in enabling the transformation of personalized medicine are discussed in detail. We suggest personalized surveillance as a novel concept to stimulate new research in both personalized medicine and biostatistics and provide several examples to illustrate statistical methods development opportunities in personalized surveillance for public health practice. Personalized medicine holds the promise of finely tailoring preventative care and therapeutic interventions for individuals rather than for the population as a whole. There is intense scientific and industrial interest in developing this framework for clinical practice. Semantic and taxonomic confusion notwithstanding, biostatisticians can play a major role in driving the required scientific developments. Epidemiologists too have a compelling stake in this fledgling field, as they strive to refine models of clinical and public health. Our goals in this chapter are to briefly introduce the principles of personalized medicine, to discuss potential roles for statisticians working in the clinical and public health arenas, and to make some suggestions for research and training. Associations of prevention, diagnosis, and treatment with proposed interventions will be denoted by p, d, and t respectively throughout this chapter.